Phytochemical characterization of the Ziziphus joazeiro Mart. metabolites by UPLC-QTOF and antifungal activity evaluation - Andrade, Jacqueline C.; dos Santos, Antí´nia T.L.; da Silva, Ana R.P.; Freitas, Maria A.; Afzal, Muhammad Inam; Gonçalo, Maria I.P.; Fonseca, Victor J. A.; Costa, Maria do S.; Carneiro, Joara N. P.; Sousa, Erlí¢nio O.; de Matos, Yedda M. L. S.; de Freitas, Thiago S.; et al. (Cellular and Molecular Biology, 2020)
The aim of this study was to evaluate the antifungal and modulatory potential of the Ziziphus joazeiro bark and leaf extracts, both in isolation and in association with fluconazole, against resistant species from the Candida genus. Antifungal assays were used to determine the half maximal inhibitory concentration (IC50) of the extract in isolation and in combination with fluconazole using the broth microdilution method and spectrophotometric readings, followed by verification of the minimum fungicidal concentration by solid medium subculture. According to the cell viability curve, both extracts inhibited fungal growth in a concentration dependent manner, in addition to showing inhibitory concentrations similar to fluconazole. However, the extracts behaved in a fungistatic manner with minimum inhibitory concentration > 8.19 mg/mL and IC50 values ranging from 0.450 mg/mL to 9 mg/mL. The minimum inhibitory concentration for both extracts decreased when in combination with fluconazole, with the AEL standing out against Candida albicans URM 4387, displaying an IC50 equal to that of fluconazole (0.002 mg/mL). Nevertheless, fluconazole antagonism was observed against the tested strains. Overall, the evaluation of both extracts against Candida spp. presented inhibitory concentration values greater than fluconazole. Moreover, despite these being chemically complex crude extracts, they did demonstrate antifungal effects and properties that concur with their ethno-biological aspect.